Graphical interface design: semiotic interpretation of the composition of elements - Obregon, Rosane de Fátima Antunes; Vanzin, Tarcisio; Ulbricht, Vânia R. (InfoDesign, 2011)
This article presents an analysis of the graphic interface of the Virtual Learning Environment in Architecture and Design - AVA_AD of Federal University of Santa Catarina, initial home page. The analysis is based on the General Theory of Signs proposed by Charles Sanders Peirce. Initially, the text presents the theoretical foundation followed by a description of the object in question. This is followed by a description of the analyzed object. Finally, the significant elements of the interface are interpreted according to the theory studied. Correlations between graphic composition and the concepts of sign in Peirce’s perspective are also presented. [ Download ]